A High-Throughput Screen Identifies a New Natural Product with Broad-Spectrum Antibacterial Activity - Ymele Leki, Patrick (2012)
Due to the inexorable invasion of our hospitals and communities by drug-resistant bacteria, there is a pressing need for novel antibacterial agents. Here we report the development of a sensitive and robust but low-tech and inexpensive high-throughput metabolic screen for novel antibiotics. This screen is based on a colorimetric assay of pH that identifies inhibitors of bacterial sugar fermentation. After validation of the method, we screened over 39,000 crude extracts derived from organisms that grow in the diverse ecosystems of Costa Rica and identified 49 with reproducible antibacterial effects. An extract from an endophytic fungus was further characterized, and this led to the discovery of three novel natural products. One of these, which we named mirandamycin, has broad-spectrum antibacterial activity against Escherichia coli, Pseudomonas aeruginosa, Vibrio cholerae, methicillin-resistant Staphylococcus aureus, and Mycobacterium tuberculosis. This demonstrates the power of simple high throughput screens for rapid identification of new antibacterial agents from environmental samples.